Bom Atom di Atas Hiroshima) Suatu Pengalaman Nyata - Arifin Bey, Arifin Bey (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1989)
The author was one of the students from occupied territories in South East Asia studying in Hiroshima when the city was atomic bombed in 1945. Tokyo was carpet-bombed in 1944-45 and foreign students were spread to other relatively safe cities. Before August 1945 Hiroshima was never bombed, but air raid alarms sounded every morning. On August 6 after the alarm was cleared the author saw a "lightning" flashed through a classroom window, and the school building, 2 km from the hypocenter, suddenly crashed, After being unconscious for a while, he noticed that the sunny morning has turned into darkness.Outside, people were running in fear and aimlessly. Some showed bleeding and others had their clothes torn or burnt. The skin of quite a few people was torn off and hanging loosely like gloves. Everything in sight was flattened to the earth and some carts were on fire. The river was full with rafts and evacuating people. Many immersed themselves in the water to alleviate the extreme heat and repetitively asked for water to drink. Most people had no clothes any more and their skin apÃ¢â¬Â¢ Reared red.Numerous people were walking among the dying and dead bodies looking for their relatives and friends. Identification was difficult due to the damaged face and decaying bodies. It took days to dispose the dead bodies by trucks. Ten days after the bombing, the students were brought to Tokyo, and here blood tests disclosed that some suffered from leucopenia. A Malayan student died in Kyoto during the trip to Tokyo.Key Words: atomic bomb-- Hiroshima -- medical effects of nuclear war -- thermal radiation -- shock wave